Contemporary transradial access practices: Results of the second international survey. Issue 7 (19th November 2018) - Shroff, Adhir R.; Fernandez, Christopher; Vidovich, Mladen I.; Rao, Sunil V.; Cowley, Michael; Bertrand, Olivier F.; Patel, Tejas M.; Pancholy, Samir B.
Abstract: Objectives: To gain insight into current practice of transradial angiography and intervention in the United States and around the world. Background: Transradial access (TRA) has grown worldwide. In a prior survey, there was significant practice variation and there was minimal US participation which limited the generalizability to US operators. Methods: We used an internet‐based survey software program to solicit input from practicing interventional cardiologists from the United States and around the world. US operators were compared with outside the United States (OUS) operators and respondent‐level comparisons were made with the prior survey to assess for temporal changes in practice. Results: Between August 2016 and January 1, 2017, 125 interventional cardiologists completed the survey representing 91 countries with the United States having 449 (39.9%) respondents. Preprocedure, noninvasive testing for collateral circulation is used more commonly in the United States (54.1%) than around the world (26.6%) but its use has decreased since 2010. In the US, 48.8% of operators never use ultrasound and 92.6% of OUS operators never use it; only 4.4% overall use ultrasound in >50% of cases. Use of bivalirudin has decreased in the US and OUS. Nearly, 30% of operators do not assess for radial artery patency following hemostasis. US respondents used TRA less commonly for primary PCI for STEMI than their global counterparts. Conclusions: There is wide variation in how TRA procedures are performed including relatively low rates of adherence to practices that are known to improve outcomes. Further education aimed at increasing use of best practices will impact patient outcomes.